Business modelling for inclusive financial services: How to enhance access to financial services for marginalised youth - Musarurwa, Hillary Jephat (GSB: Faculty, 2016)
The aim of this research was to develop a business model that will enhance the access to financial services by marginalised youth. In order to develop such a relevant business model it was necessary to understand the needs and challenges being faced by targeted clients in using and accessing formal financial services. Accessing such services will help them build assets in the long term, smooth cashflow and make savings as they transition from childhood to adulthood. Currently there are a number of barriers compounding financial exclusion and thus increasing the inequality gap. The study applied design thinking and systems thinking tools to undertake business model innovation and come out with a plausible alternative financial services model for youth and immigrants in Zimbabwe and South Africa respectively. Qualitative and quantitative research methods were applied to unpack the financial services needs of youth and how they are currently accessing service. An ethnographic approach as well as snowballing were applied in order to get to the respondents. Covert observations were done at a construction site in a bid to collect the immigrants' silent narrative of how they got to South Africa and are surviving from day to day. The research discovered that Zimbabwean youth residing in Zimbabwe and those who have migrated to South Africa are financially excluded yet they need financial services. It also discovered that there are business models being applied globally and in South Africa that are aimed at closing the financial exclusion gap. The study concluded that it is possible to have a business model that aims at serving youth, more so immigrants in South Africa, and provide them with low cost products that have a social impact on their livelihoods